Investigating the Frequency of Infantile Colic in Children with Migraine - Beiraghi Toosi, Mehran; Ghodsi, Alireza; Sarabi, Mehrdad; Ghahremani, Sara; Fazeli, Nasrin; Ghahremani, Somayeh (Journal of Child Science, 2021)
Infantile colic is a common problem observed within the first 3 months of life in infants and is a common cause of crying among infants. Migraine is a common cause of recurrent primary headaches during childhood. The pathogenesis of migraine and colic has remained unknown, but various factors seem to be involved. Patients with migraine may have a medical history of infantile colic, and infantile colic is considered an early manifestation of migraine. In this study, we investigate the frequency of history of infantile colic in 6- to 14-year-old children with migraines. In this case–control study, 80 children with the diagnosis of migraine and 100 children without migraine, all within the age range of 6 to 14 years, were included. A checklist was completed for each person about the background information and history of infantile colic as well as the history of migraine in parents. Among the children with migraine, 92.5%, and in the control group, 10%, had a familial history of migraine. Also, among the children with migraine, 61.25%, and in the control group, 4%, had a history of infantile colic. The obtained results showed that the frequency of a history of infantile colic was significantly higher in the case group than in the control group. This study provides some evidence regarding the presence of association between infantile colic as well as the familial history of migraines and developing migraines in the future. However, due to some limitations of the retrospective manner of the study, the results should be completed with future studies.
Keywords: infantile colic; migraine; child